To save or not to save: Knowledge, attitude, skills and effects of an experimental intervention on advancing first aid skills in high school students in Hue City, Vietnam - Le Duc Huy; Pham Thanh Tung; Dinh Thanh Tra; Le Nguyen Quynh Nhu; Nguyen Tuan Linh; Tran Xuan Tien; Nguyen Vu Phuong Thao; Trinh Thi Le Vy; Tran Thi Hang; Huu Hai Hoang; Vo Van Khoa; Nguyen Thi Anh Phuong; et al. (PLoS ONE, 2025)
Unintentional injury is the leading cause of death in adolescents especially in low-middle-income countries including Vietnam. However, there is limited evidence on first aid (FA) knowledge, attitude, and skills among Vietnamese adolescents. Our study aims to assess the knowledge, attitudes, and skills regarding FA; and evaluate how these domains improve after implementing FA training programs among high school students in Hue city. A single-group pre-post-intervention study was conducted on high school students between June and September 2020 in Hue City, Vietnam. The training materials were developed based on international guidance on FA and adjusted to a low-middle-income country context, particularly in Vietnam. The training program provided students with essential knowledge and skills focused on the management of common injuries in Vietnam to enhance a positive attitude toward FA. The students’ responses on FA knowledge and attitude were collected using self-reported questionnaires and FA skills were evaluated by skill checklists. At baseline (n = 806), the average score of FA knowledge, attitude, and skills over a 100-point scale were 44.0 (95% CI: 38.6, 49.5), 59.4 (95% CI: 55.5, 63.4) and 39.2 (95% CI: 35.8, 42.6) respectively. Following the intervention phase (n = 106), which included a 3-hour FA training session, a significant increase in FA skill scores was observed, with a mean difference of 37.0 points (SE: 1.6). The findings demonstrated the feasibility and significant impact of a short course of FA training on improving FA skills among high school students. The results of the multivariable regression model showed baseline scores of FA attitude, FA knowledge or having previous FA training were not significantly associated with the improvement in FA skill scores in this pre-post intervention. The study findings highlighted the low level of FA knowledge, attitude, and skills; and provided evidence of the effectiveness of FA training in improving FA skills among high school students in Hue City, Vietnam.